ANALISIS WILLINGNESS TO PAY TERHADAP BUKU ANAK BERBASIS AUGMENTED REALITY “PETUALANGAN BUDI DAN WATI” - Andam Lukcyhasnita; Dina Arfianti Siregar; Rizki Syahputra (Smart Education, 2025)
Abstract: This study aims to analyze the magnitude of Willingness to Pay (WTP) and identify the determining factors that influence it towards an augmented reality-based children's book product,